Mixed schwannoma with meningioma of the trigeminal nerve - Jain Ayushi; Suri Vaishali; Sharma Bhawani; Sharma Mehar (Wolters Kluwer Medknow Publications, 2010)
Mixed tumors composed of schwannoma and meningiomas are extremely rare and are usually associated with neurofibromatosis-2 (NF-2). So far, all the cases reported have involved the cerebello-pontine angle. Only two cases did not have a clear association with NF-2. We report a mixed tumor comprising of meningioma admixed with schwannoma in a 33-year-old male with bilateral trigeminal nerve schwannomas. The patient did not fit the existing diagnostic criteria of NF-2. The relevant literature, along with diagnostic criteria for NF-2 is discussed.